Zebrafish otolith biomineralization requires polyketide synthase. (June 2019) - Thiessen, Kevin D.; Grzegorski, Steven J.; Chin, Yvonne; Higuchi, Lisa N.; Wilkinson, Christopher J.; Shavit, Jordan A.; Kramer, Kenneth L.
Abstract: Deflecting biomineralized crystals attached to vestibular hair cells are necessary for maintaining balance. Zebrafish ( Danio rerio ) are useful organisms to study these biomineralized crystals called otoliths, as many required genes are homologous to human otoconial development. We sought to identify and characterize the causative gene in a trio of homozygous recessive mutants, no content ( nco ) and corkscrew ( csr ), and vanished ( vns ), which fail to develop otoliths during early ear development. We show that nco, csr, and vns have potentially deleterious mutations in polyketide synthase ( pks1 ), a multi-modular protein that has been previously implicated in biomineralization events in chordates and echinoderms. We found that Otoconin-90 (Oc90) expression within the otocyst is diffuse in nco and csr ; therefore, it is not sufficient for otolith biomineralization in zebrafish. Similarly, normal localization of Otogelin, a protein required for otolith tethering in the otolithic membrane, is not sufficient for Oc90 attachment. Furthermore, eNOS signaling and Endothelin-1 signaling were the most up- and down-regulated pathways during otolith agenesis in nco, respectively. Our results demonstrate distinct processes for otolith nucleation and biomineralization in vertebrates and will be a starting point for models that are independent of Oc90-mediated seeding. This study will serve as a basis for investigating the role of eNOS signaling and Endothelin-1 signaling during otolith formation. Highlights: Mutations in polyketide synthase lead to otolith agenesis in zebrafish. Neither Otoconin-90 or Otogelin are sufficient for otolith seeding and tethering. Endothelin-1 and eNOS signaling likely mediate otoconia biomineralization.